Government ownership and bank efficiency: Evidence from Germany - Gerstenkorn, Jonathan (2020)
This dissertation explores the relationship between government ownership and bank efficiency in Germany. Based on a dataset of German savings banks, which are owned by German municipalities, and cooperative banks from 2011 to 2019, estimates of cost efficiency, profit efficiency, economies of scale, and technical change are computed with stochastic frontier analysis. Savings banks are found to be less cost efficient and less profit efficient than cooperative banks. The differences in estimated average efficiency scores are about 10%, with only the difference in average cost efficiency being statistically significant. Besides being less efficient, savings banks are found to operate at increasing returns to scale on average, suggesting that the recent process of consolidation has not yet resulted in savings banks operating at an efficient size. Higher rates of technical progress have been estimated for the group of savings banks. There has, however, recently been a pronounced downward trend in the rates of technical progress. Since savings banks are institutions that are not strictly guided by the goal of profit maximisation due to the fact that they have specifically been set up to promote regional economic development and financial inclusion, the result of lower relative efficiency should be interpreted with caution.